Sagot :
Answer:
[tex]3x - \frac{1}{3} = 5 \\ 3x = 5 + \frac{1}{3} \\ (3x = \frac{16}{3} ) \div 3 \\ x = \frac{16}{9 } \\ pls \: check[/tex]
Answer:
[tex]x = \frac{16}{9 } [/tex]
Step-by-step explanation:
Move constant to the right by adding its opposite to both sides
[tex]3x - \frac{1}{3} + \frac{1}{3} = 5 + \frac{1}{3} [/tex]
Since two opposites add up to zero, remove them from the expression
[tex]3x = 5 + \frac{1}{3} [/tex]
Calculate the sum
[tex]3x = 5 + \frac{1}{3} [/tex]
[tex]3x = \frac{16}{3} [/tex]
Divide both sides of the equation by 3
[tex]x = \frac{16}{9} [/tex]